Grain for Green Program to Grassland Might Lead to Carbon Sink Leakage in the Loess Plateau - Y. Q. Ma; J. H. Li; W. Cao; L. Huang (Earth's Future)
Abstract Grain for Green Program (GFGP), China's most famous ecological program, has become the main driver of carbon sink increases. However, the potential of the carbon sink effect still lacks scenario‐based systematic estimation. By backdating the GFGP carbon sink increase in the Loess Plateau (LP) over the past 20 years, we forecast and reveal the spatial distribution of the carbon sink and the contribution of the GFGP in the “Double Carbon Target” years under three scenarios. Our results showed that places restored to forests (GFGP‐Forest) will always lead to a carbon sink increase by (33.62 Tg C for 2000–2020) 0.78–1.09 Tg C and 1.29–2.13 Tg C in 2030 and 2060, respectively. However, the places restored to grasslands (GFGP‐Grassland) will lead to an increase for 2000–2020 (72.52 Tg C), but a decrease in 2030 and 2060 (0.89–9.95 Tg C and 7.42–11.18 Tg C). This conversion is due to the combination of the decrease of the Net Primary Productivity and the increase of the heterotrophic respiration in the future, which indicates that the restoration programs involved in converting croplands into grasslands will severely decrease the carbon sink benefits and potential. In summary, it is essential to correctly quantify the carbon contribution in the LP resulting from the GFGP, and properly manage to augment the carbon sink from the GFGP‐Forest and avoid the carbon source of GFGP‐Grassland in the future. Our results highlight the hidden danger of leaking carbon sink of grasslands in a typical semi‐arid region under future climate‐changing conditions.